Association of Serum 25-Hydroxyvitamin D Level With Metabolic Phenotypes of Obesity in Children and Adolescents: The CASPIAN-V Study - Esmaili, Haleh; Heshmat, Ramin; Ejtahed, Hanieh-Sadat; Rastad, Hadith; Motlagh, Mohammad Esmaeil; Asayesh, Hamid; Jafarnejad, Marzieh; Seif, Ehsan; Qorbani, Mostafa; Kelishadi, Roya (Frontiers in Endocrinology, 2020)
Background and objective: Different metabolic phenotypes of obesity are related to cardio-metabolic risk factors in children and adolescents. Vitamin D, as one important factor, could be related to different subgroups of metabolic obesity and might affect metabolic disorders. The purpose of this study was to evaluate the relationship between serum 25- hydroxyvitamin D concentration and subsets of metabolic phenotypes of obesity in children and adolescents. Methods: This nationwide cross-sectional study was conducted in the framework of the fifth survey of a national surveillance program, the CASPIAN study. Overall, 2594 students aged 7–18 years were assessed for 25-hydroxy vitamin D status. Metabolic syndrome (MetS) was defined according to the ATP III criteria modified for the pediatric age group. Participants were classified into four metabolic phenotypes of obesity according to categories of the BMI and metabolic status, : “metabolically healthy obese” (MHO), “metabolically non-healthy non-obese” (MNHNO), “metabolically non-healthy obese” (MNHO), and metabolically healthy non-obese (MHNO). Multinomial logistic regression analysis was performed for evaluating the association of 25-hydroxyvitamin D status with different metabolic phenotypes of obesity. Results: In this study, 85.2% of participants were classified as MHNO, 11.0 % as MHO, 2.5% as MNHNO, and 1.3% as MNHO. The frequency of hypovitaminosis D was more prevalent in MNHO (85.3%) than in other phenotypes (MHNO: 70%; MHO: 76.5%; MNHNO: 78.1%, respectively, P<0.05). In the multivariate model, hypovitaminosis D significantly increased the odds of being MHO (OR: 1.46; 95% CI: 1.07-1.77) and MNHO (OR: 2.89; 1.05-8.31) compared to the healthy group. Likewise, in multivariate model, per each unit (ng/mL) increment in 25-hydroxy vitamin D concentration, the odds of MNHNO and MNHO decreased significantly by 7% (OR: 0.93; 0.91-0.96) and 6% (OR: 0.94; 0.91-0.98) respectively. Conclusion: Our results support the hypothesis that 25-hydroxyvitamin D concentration is associated with metabolic obesity phenotypes. Longitudinal studies are necessary to assess the clinical impacts of this finding.